Quantum chemical interpretation of redox properties of ruthenium complexes with vinyl and TCNX type non-innocent ligands - Záliš, Stanislav; Winter, Rainer F.; Kaim, Wolfgang (Coordination chemistry reviews, 2010)
This review provides an overview of density functional theory (DFT) calculations in a consequence with spectroelectrochemical measurements on mononuclear and symmetrically or unsymmetrically bridged di- and tetranuclear ruthenium complexes of vinyl and TCNX ligands. The DFT approach is used for the calculations of molecular structures, vibrational frequencies, electronic and electron paramagnetic resonance (EPR) spectral data. DFT calculations enable us to identity the primary redox site and the electron and spin-density distribution between the individual components for the individual redox congeners. The DFT technique reproduces the spectral properties of the presented complexes and their radical ions. The generally close correspondence between experimental and quantum chemical results demonstrate that modern DFT is a powerful tool to address issues like ligand non-innocence and electron and spin delocalization in systems containing both redox-active metal ions and redox-active ligands.